The Influence of Fintech and Financial Behavior on MSMEs Financial Performance with Financial Literacy as a Mediating Variable: A Study of the Sukorejo Smart Community - Rafi Nur Hadi Kusuma; Miftahul Huda (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid development of financial technology (fintech) has transformed financial management practices among micro, small, and medium enterprises (MSMEs); however, technology adoption alone may be insufficient to improve financial performance without adequate financial capabilities. This study examines the effects of fintech and financial behavior on MSME financial performance and assesses the mediating role of financial literacy within the Sukorejo Smart Community. A quantitative associative design was employed, involving all 42 active MSME members selected through saturated sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with multiple linear regression and path analysis in SPSS, supplemented by the Sobel test to assess mediation effects. The findings indicate that fintech and financial behavior have positive and significant effects on financial literacy. Fintech, financial behavior, and financial literacy also have positive and significant effects on MSME financial performance. Furthermore, financial literacy significantly mediates the effects of both fintech and financial behavior on financial performance. The study concludes that effective fintech adoption and sound financial behavior improve MSME financial performance both directly and indirectly by strengthening financial literacy. These findings clarify the explanatory role of financial literacy in linking digital financial adoption and financial behavior to MSME outcomes and underscore the need for integrated initiatives that combine fintech adoption with financial literacy development.